Konsep Pemeliharaan Allah Terhadap Alam dan Manusia Serta Implikasinya Dalam Pendidikan Islam - Ilham Agustian Widia Yusuf; Fardan Abdul Basith; Heru Nugraha; Adang Hambali; Hasan Basri (Journal of Education and Social Culture, 2025)
Education is the main institution that plays an important role in building and developing civilization. According to the perspective of the Qur'an, monotheism is the main root that must provide energy to all aspects of life. All life activities must depart from this monotheism, including educational activities and implementation. The aim of writing this paper is to analyze the concept of God's care for nature and humans. This research method uses a qualitative approach with literature studies through explanations of interpretations to explain the concept of God's care for nature and humans in the Al-Qur'an, then has implications for Islamic education. The research results show that the Al-Qur'an contains the concept of God's care for nature and humans and its implications in Islamic education which are contained in the concept of tauhid rububiyyah. From a monotheistic perspective, the universe is created and managed by the will and attention of Allah. The Rububiyyah nature of Allah covers the entire universe and its contents, which maintains and regulates all creatures. Believing in the Rububiyyah of Allah will foster in a Muslim sincerity in worshiping Him and complete submission before Him.